A CASE REPORT NEEDLEFISH BITE WOUND TO THE LEFT PELVIC REGION - Joestiantho Laurenz Kilmanun; Gregorius Batara P.S. Sutardi (Pattimura University, 2022)
Introduction : Needlefish are predatory schooling fish with long slender jaws that have been known to leap out of the surface of the water at high speeds. Needlefish (Family Belonidae) are carnivorous fish that have long beaks that are studded with teeth, elongated bodies measuring up to 2 m, and live in temperate waters. Benefits of the emergency debridement and antibiotic prophylaxis. Case illustration : A 30-year-old male, fisherman by profession, presented 7 h after an odd accident while at sea. He gave a history of being injured by the horn of a 2-ft-long needlefish, which rose above the water and went through the right pelvic region. Clinical examination revealed an entry wound of 3x5 cm based on bone. The patient was hemodynamically unstable and in pain. The routine biochemical parameters in his blood were normal. We did the emergency resuscitation and debridement with local anesthesia in primary health care. The patient was hemodynamically stable 40 hours after debridement. We gave antibiotics, pain management, and tetanus prophylaxis. The patient was discharged home and 1 week after the accident there was no complaint. Conclusion : While rare, Needlefish related injuries can have clinical sig nificance in excess of their external appearance. Injuries caused by Needlefish and other fish should be considered when the patient’s injury history is consistent with a possible injury by a Needlefish or similar organism. The diagnosis was prompt, and even though the presentation to the casualty was delayed, immediate resuscitative measures and surgery ensured successful management of the patient.